2021
DOI: 10.1085/jgp.202112902
|View full text |Cite
|
Sign up to set email alerts
|

ENaC and ROMK channels in the connecting tubule regulate renal K+ secretion

Abstract: We measured the activities of epithelial Na channels (ENaC) and ROMK channels in the distal nephron of the mouse kidney and assessed their role in the process of K+ secretion under different physiological conditions. Under basal dietary conditions (0.5% K), ENaC activity, measured as amiloride-sensitive currents, was high in cells at the distal end of the distal convoluted tubule (DCT) and proximal end of the connecting tubule (CNT), a region we call the early CNT (CNTe). In more distal parts of the CNT (aldos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Meanwhile, ROMK and ENaC activity increase in the downstream CCD. These data support the idea that a high-K + diet could increase the risk of hypertension due to overactivated sodium reabsorption channels [ 180 ]. Another study conducted in rats reported that heterozygous ROMK disruption may lead to reduced blood pressure and less severe renal injury.…”
Section: Wnk Interactive Channels In the Thick Ascending Limb (Tal)supporting
confidence: 87%
“…Meanwhile, ROMK and ENaC activity increase in the downstream CCD. These data support the idea that a high-K + diet could increase the risk of hypertension due to overactivated sodium reabsorption channels [ 180 ]. Another study conducted in rats reported that heterozygous ROMK disruption may lead to reduced blood pressure and less severe renal injury.…”
Section: Wnk Interactive Channels In the Thick Ascending Limb (Tal)supporting
confidence: 87%
“…In a recent study, Yang and coworkers studied ENaC and ROMK activities along the distal nephron on various K + diets. ENaC-dependent K + secretion shifted from the early CNT under basal to more distal parts of the CNT under increased K + intake [32 ▪▪ ].…”
Section: Physiological Function Of the Three Epithelial Sodium Channe...mentioning
confidence: 90%
“…Potassium is freely filtered through the glomerulus and into the nephrons. As the luminal fluid passes through the nephrons, various regulatory processes control how much K + is secreted or reabsorbed [7][8][9]. A schematic of renal K + handling is shown in Fig.…”
Section: Kidney Functionmentioning
confidence: 99%
“…However, the distal tubule's capacity to reabsorb K + is limited (up to 3% of filtered K + in male rats), meaning that in times of drastically low K + intake, it is up to the downstream collecting duct to conserve K + via reabsorption [7,8].…”
Section: Kidney Functionmentioning
confidence: 99%